Trachyonychia In Children : A Study In Fourteen Patients - Dhar Sandipan; Malakar Subrata; Dhar Subhra (Wolters Kluwer Medknow Publications, 2001)
Fourteen patients, 8 girls and 6 boys with trachyonychia have been reported. Their ages ranged from 5 to12 years; mean 8.5 years. All of them had retarded growth of nail plates with roughness. Fragility blackish discoloration, longitudinal ridging of all the 20 nails of fingers and toes. Six patients had thickening of the nail plates while 8 had thinning. In one patient each oil drop sign and splinter haemorrhages were seen; two patients each had associated lichen planus and psoriasis and one each atopic dermatitis, vitiligo and alopecia areata. Personal history of atopy was obtained in 6 patients. Nail biopsy carried out in 5 patients revealed nonspecific histology. Radiological examination of fingers and toes revealed no bony or joint abnormality. The nail changes remained almost static during a 4 year follow-up period.